THU0020 Tocilizumab decreases the pro-inflammatory role of platelets in rheumatoid arthritis: identification of a new mechanism of action associated with positive response?. (12th June 2018) - Prum Delepine, C.; Derambure, C.; Vidal, F.; Pinta, A.; Pau, D.; Conde da Silva Fraga, E.; Boyer, O.; Senbel, E.; Gaudin, P.; Vittecoq, O.; Lequerre, T.
Abstract : Background: Tocilizumab (TCZ), a humanised monoclonal antibody directed against IL-6 receptor, is an efficient treatment for rheumatoid arthritis (RA) but its mechanisms of action are not yet well understood. Objectives: To identify new mechanisms of action of TCZ, by the study of gene expression fluctuations, between baseline (BL) and 3 months of treatment (T3m ), in RA patients. Methods: TOSCA study has been realised to evaluate efficiency and tolerance of TCZ administrated subcutaneously in active RA patients. Among the 125 patients of TOSCA study, 38 were ranked according to their treatment response after 3 months: 29 good responders (GR), 19 of which were also treated by methotrexate (MTX) and 10 non responders (NR), 7 of which were treated by MTX (GR: DAS 28-ESR3m <3, 2 and Delta DAS28-ESR(BL-3m) ≥3; NR: DAS 28-ESR>3, 2 and Delta DAS28-ESR(BL-3m) <3). A transcriptomic analysis was performed using a 44K whole human genomic DNA microarray (Agilent) on whole blood cells collected at BL and at T3m . We identified genes with statistically significant expression fluctuations between BL and T3m specifically in GR group (and not in NR group), treated by TCZ in monotherapy (excluding genes which fluctuated only with the association TCZ-MTX). Functional bio-informatics analysis was applied to this set of transcripts, by interrogation of Gene Ontology database, using Single Experiment Analysis tool and Natural Language Processing algorithms. Results: Overall, 1089 transcripts significantly dysregulated were identified only in GR group at T3m (t test, p<0.05). This first set of transcripts was reduced to 783 by exclusion of transcripts that were fluctuated specifically when MTX was associated with TCZ in GR group. The functional analysis with these 783 genes dysregulated under TCZ in monotherapy enabled the identification of 8 transcripts ( CLU, F13A1, ITGA2B, ITGB3, SELP, SNCA, SPARC, TREML1 ) whose relative abundances were significantly reduced at T3m. These genes were enriched in "platelet alpha granule" GO functional category. Proteins encode by these genes, either released in blood circulation or expressed at the cell membrane in case of platelet activation, have a pro-inflammatory activity through an interaction between platelets and immune cells. Conclusions: This transcriptomic analysis suggests a new mechanism of action of TCZ in RA and the importance of platelets activation in RA pathophysiology. Indeed, genes linked with the pro-inflammatory role of platelets were down regulated. Further functional studies will be necessary to validate the direct effect of TCZ on platelets in RA. Acknowledgements: The authors would like to thank the SFR (Société Française de Rhumatologie) for the attribution of research fellowship and Roche, France, for the support by a grant. Disclosure of Interest: C. Prum Delepine: None declared, C. Derambure: None declared, F. Vidal: None declared, A. Pinta Employee of: Roche Laboratory, D. Pau Employee of: Roche Laboratory, E. Conde da Silva Fraga Employee of: Roche Laboratory, O. Boyer: None declared, E. Senbel: None declared, P. Gaudin: None declared, O. Vittecoq: None declared, T. Lequerre Grant/research support from: Roche Laboratory